Analysis of The Cost and Economic Returns in Rice Production in Ebonyi State, Nigeria - Nwahia, Ogechi Cordelia (Indonesian Journal of Agricultural Research, 2020)
Low profit from most staple food production in Nigeria, have continued to discourage the teaming unemployed Nigerian youth from taking up farming as a business. Therefore, this study analyzes the cost and economic returns in Ebonyi State rice production. This study made used of simple random sampling techniques to select 242 rice farmers. The study employed the use of structured questionnaire in its primary data collection. The collected data were analyzed using descriptive statistics (Percentages, Frequency, Standard deviation and Mean), Net Rice Farming Income (NRFI) and Returns/US Dollar Invested (RUSDI). The result from the analysis reveals that rice production is profitable in Ebonyi state. The Net Rice Farming Income (NRFI) obtained by the farmers in Ebonyi state were $900.10 US Dollar per hectare while the return on investment obtained by them were $2.90 US Dollar per hectare. Therefore, unemployed youth in Nigeria should be encourage through provision of rice farming grant or loan by the government. In addition, adequate training on improve technology should be conducted by the government agency for the rice farmers.